Depression, Mindfulness, and Psilocybin: Possible Complementary Effects of Mindfulness Meditation and Psilocybin in the Treatment of Depression. A Review - Heuschkel, Kristin; Kuypers, Kim P.C. (Frontiers in Psychiatry, 2020)
Depression is a major public health problem that affects approximately 4.4% of the global population. Since conventional pharmaco- and psychotherapies are only partially effective, as demonstrated by the number of patients failing to achieve remission, alternative treatments are needed. Mindfulness meditation (MM) and psilocybin represent two promising novel treatments that might even have complementary therapeutic effects when combined. Since the current literature is limited to theoretical and empirical underpinnings of either treatment alone, the present review aimed to identify possible complementary effects that may be relevant to the treatment of depression. To that end, the individual effects of mindfulness meditation (MM) and psilocybin, and their underlying working mechanisms were compared on a non-exhaustive selection of six prominent psychological and biological processes that are well-known to show impairments in patients suffering from major depression disorder, that is mood, executive functioning, social skills, neuroplasticity, core neural networks, and neuroendocrine and -immunological levels. Based on predefined search strings used in two online databases (Pubmed and Google Scholar) 1129 articles were identified. After screening title and abstract for relevance related to the question, 82 articles were retained and 13 were added after reference list search, resulting in 95 articles included in the review. Findings show that MM and psilocybin exert similar effects on mood, social skills and neuroplasticity; different effects were found on executive functioning, neural core networks, and neuroendocrine and –immune system markers. Potential mechanisms of MM’s effects are enhanced affective self-regulation through mental strategies, optimisation of stress reactivity, and structural and functional adjustments of prefrontal and limbic areas; psilocybin’s effects might be established via attenuation of cognitive associations through deep personal insights, cognitive disinhibition, and global neural network disintegration. It is suggested that when used in combination, MM and psilocybin could exert complementary effects by potentiating or prolonging mutual positive effects for example, MM potentially facilitating psilocybin-induced peak experiences. Future placebo-controlled double-blind randomized trials focussing on psilocybin-assisted mindfulness-based therapy will provide knowledge about whether the proposed combination of therapies maximises their efficacy in the treatment of depression or depressive symptomatology.